Elevated levels of plasma homocysteine, deficiencies in dietary folic acid and uracil–DNA glycosylase impair learning in a mouse model of vascular cognitive impairment - Jadavji, Nafisa M.; Farr, Tracy D.; Lips, Janet; Khalil, Ahmed A.; Boehm-Sturm, Philipp; Foddis, Marco; Harms, Christoph; Füchtemeier, Martina; Dirnagl, Ulrich (Elsevier, 2015)
Dietary deficiencies in folic acid result in elevated levels of plasma homocysteine, which has been associated with the development of dementia and other neurodegenerative disorders. Previously, we have shown that elevated levels of plasma homocysteine in mice deficient for a DNA repair enzyme, uracil–DNA glycosylase (UNG), result in neurodegeneration. The goal of this study was to evaluate how deficiencies in folic acid and UNG along with elevated levels of homocysteine affect vascular cognitive impairment, via chronic hypoperfusion in an animal model. Ung+/+ and Ung−/− mice were placed on either control (CD) or folic acid deficient (FADD) diets. Six weeks later, the mice either underwent implantation of microcoils around both common carotid arteries. Post-operatively, behavioral tests began at 3-weeks, angiography was measured after 5-weeks using MRI to assess vasculature and at completion of study plasma and brain tissue was collected for analysis. Learning impairments in the Morris water maze (MWM) were observed only in hypoperfused Ung−/− FADD mice and these mice had significantly higher plasma homocysteine concentrations. Interestingly, Ung+/+ FADD produced significant remodeling of the basilar artery and arterial vasculature. Increased expression of GFAP was observed in the dentate gyrus of Ung−/− hypoperfused and FADD sham mice. Chronic hypoperfusion resulted in increased cortical MMP-9 protein levels of FADD hypoperfused mice regardless of genotypes. These results suggest that elevated levels of homocysteine only, as a result of dietary folic acid deficiency, don’t lead to memory impairments and neurobiochemical changes. Rather a combination of either chronic hypoperfusion or UNG deficiency is required.